The relationship of stock market among Southeast Asia to Malaysia stock market: analysis based on large capital index - Ishak, Muhammad Noor Izami (2012)
The aim of this study is to investigate the relationship between Indonesia Stock Exchange Large Capital Index, Stock Exchange of Thailand Large Capital Index, Singapore Exchange Large Capital Index and Philippines Stock Exchange Large Capital Index to the FTSE Bursa Malaysia KLCI Index. The study used Simple Linear Regression and Multiple Linear Regression in order to find the relationship among those markets. The daily closing price of stock indices is collected from 1st January 2007 until 31st December 2011. From the result, it reveals that all these stock indices have a significant positive relationship towards FTSE Bursa Malaysia KLCI Large Capital Index. It means that there are interdependencies among this Southeast Asia stock market in term of large capital index. the stock market in Southeast These results further our understanding of the relationship between Asia and should be useful for regulator, investor and speculator.